A simple PCR-based method for the rapid and accurate identification of spider mites (Tetranychidae) on cassava - Ovalle, Tatiana M. (Sci Rep, 2020)
The morphological identification of mites entails great challenges. Characteristics such as dorsal setae and aedeagus are widely used, but they show variations between populations, and the technique is time consuming and demands specialized taxonomic expertise that is difficult to access. A successful alternative has been to exploit a region of the mitochondrial cytochrome oxidase I (COI) gene to classify specimens to the species level. We analyzed the COI sequences of four mite species associated with cassava and classified them definitively by detailed morphological examinations. We then developed an identification kit based on the restriction fragment length polymorphism–polymerase chain reaction of subunit I of the COI gene focused on the three restriction enzymes AseI, MboII, and ApoI. This set of enzymes permitted the simple, accurate identification of Mononychellus caribbeanae, M. tanajoa, M. mcgregori, and Tetranychus urticae, rapidly and with few resources. This kit could be a vital tool for the surveillance and monitoring of mite pests in cassava crop protection programs in Africa, Asia, and Latin America.